Aplikasi IAA Terhadap Kecepatan Tumbuh Asal Bibit Bud Chip Tebu (Saccharum officinarum L.) di Persemaian Pottray - Sigit Eko Prasetyo; Wiwik Indrawati; Made Same (Jurnal Agro Industri Perkebunan, 2020)
This study was conducted at the Politeknik Negeri Lampung in December to February 2019. The research used factorial Randomized Block Design (RBD) with two factor and three replication.The first factor is the source of bud chip derived from the 3 part: B1 (top), B2 (middle), B3 (bottom) and the second factor is the concentration of IAA with 4 levels of A0 (0 mg.l-1), A1 (150 mg.l-1), A2 (300 mg.l-1), and A3 (450 mg.l-1). The observed variable is speed of growing eye buds, percentage of growing buds, height of the plant, number of leaves, and diameter of stem. The results of study showed the origin of bud chip seed middle part has the best growth of variable speed grow, precentage of growth, high seeding, number of leaves, and diameter of the stem. IAA administration at concentrations 0-450 mg.l-1 which has been applied to the source of bud chip upper, middle, and lower with immersion treatment for 20 minutes does not give a noticeable impact on the growing speed, precentage of growing, height plant, number of leaves, diameter of stem. There is no interaction between the origin of bud chip seed (top, middle, bottom) and IAA concentration.